1986
DOI: 10.1159/000287939
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Alexithymic Characteristics from Physiological, Personality, and Subjective Measures

Abstract: Noting concerns for a comprehensive conceptualization of alexithymic characteristics, the present study examines the potential utility of considering these characteristics as manifestations of deficits in cognitive schemata. Research guided by this conceptualization has identified physiological, subjective, and personality features of alexithymic characteristics. It is reasoned that if this conceptualization has merit, it should be possible to predict the presence of alexithymic characteristics from these feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…alone or with family, could be an indication of social support and may be another mediator that fostered depression. In studying a nonpatient population, Martin et al [1986] found social introversion, a fac tor which may foster lack of social support, to be one of the variables in a regression model that predicted alexithymia measured by the SSPS. Less social support may be related to living alone, and there is data to suggest that less social support augments de pression [Brown and Harris, 1978].…”
Section: Discussionmentioning
confidence: 99%
“…alone or with family, could be an indication of social support and may be another mediator that fostered depression. In studying a nonpatient population, Martin et al [1986] found social introversion, a fac tor which may foster lack of social support, to be one of the variables in a regression model that predicted alexithymia measured by the SSPS. Less social support may be related to living alone, and there is data to suggest that less social support augments de pression [Brown and Harris, 1978].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from laboratory studies of the responses of alexithymic individuals to stress does not, however, provide unequivocal support for the prediction of increased sympathetic activity. Although some authors have concluded that affected individuals do experience elevated autonomic activity in response to stressinducing experimental paradigms~Martin & Pihl, 1986;Martin, Pihl, Young, Ervin, & Tourjman, 1986;Rabavilas, 1987!, others have found evidence that contradicts this notion, and some have even concluded that alexithymic individuals exhibit less autonomic reactivity than controls under conditions of stress~Hyer, Woods, Summers, & Boudewyns, 1990;Newton & Contrada, 1994;Papciak, Feuerstein, & Spiegel, 1985!. The inconsistency of these findings may be due in part to the use of various, poorly standardized measures of alexithymia.…”
mentioning
confidence: 99%
“…Results pertaining to nonclinical subjects' alexithymic orientations reveal that persons having high, but nonclinical, ranges of alexithymia lack an awareness of affect cues to guide communication; lack implementation of emotion in personal relationships; and lack intensity of emotional arousal (Yelsma, 1992), in addition to having diminished self-esteem (Yelsma, 1995). Martin, Pihl, Young, Ervin, and Tourjman (1986) investigated the physiological and psychological characteristics of alexithymic subjects' interpersonal behaviors. Conclusions drawn from their comprehensive overview of individuals having high scores on assessments of alexithymia suggest an "elevated level of sympathetic activity, reduced expression and experience of affect relative to neuroticism, poor interpersonal skills marked by over control, tension, and withdrawal .…”
Section: Alexithymia and Interpersonal Communicationmentioning
confidence: 99%